2020
DOI: 10.1002/jez.2403
|View full text |Cite
|
Sign up to set email alerts
|

Thermal physiology responds to interannual temperature shifts in a montane horned lizard, Phrynosoma orbiculare

Abstract: As climate change marches on, rapidly rising temperatures shatter records every year, presenting ever‐growing physiological challenges to organisms worldwide. Ectotherms rely on behavioral and physiological plasticity to contend with environmental fluctuations. Nonetheless, our understanding of thermal plasticity has been largely limited to laboratory settings. Here, we test whether aspects of thermal physiology respond to interannual shifts in thermal environment in a natural population of Phrynosoma orbicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…For example, several species of Pristimantis frogs display similar rates of evolutionary change in both CT max and CT min when accounting for microclimatic temperature variations (Pintanel et al, 2019), suggesting that CT max evolution might not be as conserved as previously thought (Araújo et al, 2013; Gunderson et al, 2018; Hoffmann et al, 2013). Lability in thermal traits has also been identified in other taxa, including newts and numerous lizard species (Clusella‐Trullas & Chown, 2014; Domínguez–Guerrero et al, 2020; Gvoždík, 2012). Research in the past few decades has robustly demonstrated that physiological diversity is actually a mosaic of evolutionary patterns and rates; the key question resides in identifying the processes sculpting these differences in the tempo and mode of physiological evolution.…”
Section: Introductionmentioning
confidence: 92%
“…For example, several species of Pristimantis frogs display similar rates of evolutionary change in both CT max and CT min when accounting for microclimatic temperature variations (Pintanel et al, 2019), suggesting that CT max evolution might not be as conserved as previously thought (Araújo et al, 2013; Gunderson et al, 2018; Hoffmann et al, 2013). Lability in thermal traits has also been identified in other taxa, including newts and numerous lizard species (Clusella‐Trullas & Chown, 2014; Domínguez–Guerrero et al, 2020; Gvoždík, 2012). Research in the past few decades has robustly demonstrated that physiological diversity is actually a mosaic of evolutionary patterns and rates; the key question resides in identifying the processes sculpting these differences in the tempo and mode of physiological evolution.…”
Section: Introductionmentioning
confidence: 92%
“…Body temperatures in lizard species overall tend to follow temporal environmental temperature patterns, such as within a day, or across seasons or years (Clusella-Trullas and Chown 2014;Domínguez-Guerrero et al 2020), yet the stability or steepness of this relationship can vary depending on the number of predators or competitors present (Salazar et al 2019). In this regard, our observations suggest body temperatures follow increases in environmental temperatures regardless of predation exposure.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, body temperatures in lizard species overall tend to follow temporal environmental temperature patterns, such as within a day, or across seasons or years (Clusella‐Trullas & Chown 2014; Domínguez‐Guerrero et al . 2020), yet the stability or steepness of this relationship can vary depending on the number of predators or competitors present (Salazar et al . 2019).…”
Section: Discussionmentioning
confidence: 99%